Delineating of Groundwater Aquifer Potential Using Vertical Electrical Sounding (VES) Methods in Giriloyo, Wukirsari Village, Imogiri District, Bantul Regency, Special Region of Yogyakarta - Kiswiranti, Desi; Tania, Dina; Dzakiya, Nurul; Hanani, Prita (Politeknik Negeri Batam, 2023)
The geophysical investigation in Giriloyo, Wukirsari Village, has defined the groundwater potential zones. The research region underwent a geophysical examination utilizing the electrical resistance method, which comprised the vertical electrical sounding (VES) technique and the Schlumberger array system. The study area is surrounded by common rock types such as lava, tuff, agglomerate, and alluvial. In the study region, five lines were explored. Data for subsurface resistivity were gathered with an Oyo McOhm type 2115. IPI2win, a piece of computer software that analyzes data and automatically interprets apparent resistivity, was used to examine the data. The VES data showed the varied nature of the subsurface geological sequence. The geoelectrical cross-sections along the profile of (VES 2-3-4-1) show an aquifer, which stretches from the southeast towards the northwest part of the basin. Tuff is seen to have formed shallow aquifers due to the top weathered part at VES-2 and 3, while Quartz chlorite calcite (VES-4) and Plagioclases (VES-1) are devoid of shallow aquifers. The higher-elevation lithological areas recharge the low-elevation aquifer zones. At VES 2 and 3, relatively low resistivity values (< about 100 Ωm) have been observed. A field observation at these locations reveals that these lithologies are highly fractured with a weathering profile of up to 10 m. Thus, these are the sites where groundwater potential zones can be marked (figure 4). The high resistivity (about 3162 Ωm regions is observed extending at the VES-4; this may be due to the least weathered Quartz chlorite calcite at high elevation. VES-1 is also located on the plagioclase and shows a slight resistivity zone, which could be considered a groundwater recharge zone. This profile shows the high possibility of groundwater potential due to the zone of lineaments.